PERADILAN GAMPONG SEBAGAI WADAH DALAM MENYELESAIKAN SENGKETA WARISAN DI PROVINSI ACEH - Rahmat Fitrah (Jurnal Public Policy, 2017)
Legally, it is known there are two ways of settling disputes, first settling disputes in litigation that is in court, and both are known by way of non-litigation dispute resolution outside the court that. With the existence of alternative dispute resolution such as non-litigation, the court only used as a last choice by the parties to resolve the dispute. In Aceh disputes in society more dominant resolved through Customary Council, as a matter of dispute inheritance, because according to them more in line with a growing sense of justice in society. Keyword: Justice Gampong,Resolving Disputes.